The Importance of Anthropogenic Influence in Assessing the Ecological Condition of Cities in Uzbekistan (in the Case of Navoi) - Normurod Faxriddin o’g’li Latipov; Nilufar Karshiboevna Komilova (مجلة بغداد للعلوم, 2024)
Creating a series of maps, grouping ecological indicators, and assessing cities' environmental status are considered very relevant research tasks. A growing population in cities, the establishment of various industrial and production enterprises, and the use of vehicles all contribute to the degradation of the environment. Navoi region is a young administrative unit located in central Uzbekistan. Regarding industrial development, it ranks first among administrative units in the republic. Production in its cities, especially the high productivity of heavy industrial enterprises, ecological problems in various forms due to human pressure on the natural environment, and the health of the population - mothers and children, and the elderly - pose a serious threat. As a result of high anthropogenic pressure, ecologically clean green areas are decreasing. It occupies a very small share compared to the total area. This, in turn, can cause environmental stress in regional cities located in arid regions, and cause the loss of greenery. Anticipating such consequences and combating them is particularly important today. This article analyzes environmental conditions in the Navoi region and its cities, as well as the most significant factor affecting them, the anthropogenic effects. The land classification was made for the city area, as well as suggestions and recommendations. For this, we analyzed and grouped the structural classification of the area of regional cities. As a result of our research, we can see that environmental risk is high. In this article, the main parameters of the study are covered with accurate calculations.